Acquisition of Daptomycin Resistance by Enterococcus faecium Confers Collateral Sensitivity to Glycopeptides - Zeng, Weiliang; Feng, Luozhu; Qian, Changrui; Chen, Tao; Wang, Sipei; Zhang, Ying; Zheng, Xiangkuo; Wang, Lingbo; Liu, Shixing; Zhou, Tieli; Sun, Yao (Frontiers in Microbiology, 2022)
Daptomycin is a last-line antibiotic used in the treatment of multidrug-resistant Enterococcus faecium infections. Alarmingly, daptomycin-resistant E. faecium isolates have emerged. In this study, we investigated the evolution and mechanisms of daptomycin resistance in clinical E. faecium isolates, as well as the corresponding acquisition of collateral sensitivity (CS) as an evolutionary trade-off. We evolved daptomycin resistance in six daptomycin-susceptible E. faecium isolates to obtain daptomycin-resistant mutants. The six E. faecium strains successfully acquired high-level resistance to daptomycin in vitro, but this led to fitness costs in terms of growth, in vitro competition, and virulence. Mutations in liaFSR, yycFG, and cls; increased surface positive charge; thicker cell walls; and elevated expression of dltABCD and tagGH were observed in daptomycin-resistant mutants. Surprisingly, we observed the emergence of CS in SC1762 isolates after the induction of daptomycin resistance. Compared to parental strains, the SC1174-D strain (daptomycin-resistant mutant of SC1174; non-CS) showed significantly up-regulated expression of the vanA gene cluster. However, in SC1762-D (daptomycin-resistant mutant of SC1762), all vanA cluster genes except the vanX gene were obviously down-regulated. Further in silico analyses revealed that an IS1216E-based composite transposon was generated in SC1762-D, and it disrupted the vanH gene, likely affecting the structure and expression of the vanA gene cluster and resulting in re-sensitization to glycopeptides. Overall, this study reports a novel form of CS between daptomycin and glycopeptides in E. faecium. Further, it provides a valuable foundation for developing effective regimens and sequential combinations of daptomycin and glycopeptides against E. faecium.